Impact of the COVID-19 pandemic on the psychological well-being of adolescents by gender identity - Cinta Folch; Fabiana Ganem; Andreu Colom-Cadena; Isabel Martínez; Carmen Cabezas; Jordi Casabona (Gaceta Sanitaria, 2023)
Objective: To describe the impact of the COVID-19 pandemic on the psychological well-being of adolescents in Catalan schools by gender identity, and to compare coping strategies adopted to manage the health crisis and their relationship with the self-perceived impact of COVID-19 on mental health. Method: Cross-sectional study in educational centres that includes 1171 adolescents over 15 years old from October to November 2021. Multivariate logistic regression models were built to evaluate the association between coping strategies with self-perceived impact of the pandemic on mental health. Results: A greater proportion of girls perceived a worsening in mental health than boys due to COVID-19 (36.9% and 17.8%, respectively). The main emotions reported for both girls and boys were worry and boredom. The study found an association between positive coping strategies with less adverse mental health among girls, whereas unhealthy habits were associated with a higher probability of declaring worsening of mental health for both girls and boys. Conclusions: This study demonstrated the negative impact of the COVID-19 pandemic on psychological well-being in adolescents and a clearly worse impact on girls. It is important to keep monitoring the medium- and long-term secondary impacts of the pandemic on mental health outcomes of adolescents and to gather information that can improve services for the development of healthy coping strategies during health crises like COVID-19, which include gender perspective. Resumen: Objetivo: Describir el impacto de la COVID-19 en el bienestar emocional de adolescentes en Cataluña y comparar las estrategias de afrontamiento adoptadas durante la pandemia y su relación con el impacto autopercibido de la COVID-19 en la salud mental según identidad de género. Método: Estudio transversal en centros educativos de Cataluña incluyendo 1171 alumnos/as mayores de 15 años, de octubre a diciembre de 2021. Mediante modelos de regresión logística multivariante se evaluó la asociación entre las estrategias de afrontamiento y el impacto autopercibido de la pandemia en la salud mental. Resultados: Una mayor proporción de chicas que de chicos percibía un empeoramiento en su salud mental por la COVID-19 (36,9% y 17,8%, respectivamente). Las principales emociones reportadas tanto en chicas como en chicos fueron preocupación y aburrimiento. Se observó una asociación entre estrategias de afrontamiento positivas y una menor probabilidad de declarar un empeoramiento en la salud mental a raíz de la pandemia en las chicas, mientras que otras estrategias relacionadas con hábitos poco saludables se asociaron a una mayor probabilidad de declarar un empeoramiento de la salud mental en chicas y chicos. Conclusiones: Este estudio demuestra el impacto negativo de la pandemia de COVID-19 en el bienestar psicológico de los/las adolescentes, especialmente en las chicas. Es importante seguir monitorizando el impacto de la COVID-19 a medio y largo plazo en la salud mental de los/las adolescentes y disponer de información que pueda mejorar los servicios para el desarrollo de estrategias de afrontamiento saludables durante crisis de salud como la COVID-19 considerando una perspectiva de género.